2020
DOI: 10.4028/www.scientific.net/msf.1010.286
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Carbide-Nickel (WC-Ni) Coating as Potential Wear and Corrosion Protection for Metal

Abstract: Tungsten carbide-based composite / cermet coatings have been deposited to improve metal properties such as hardness, corrosion resistance, and wear resistance. In this study, the evaluation of two deposition methods, which are high velocity oxy-fuel (HVOF) and electrodeposition (ED) is done to compare their performance as metal protection from corrosion and wear. The HVOF powder was deposited using oxygen and natural compress gas and sprayed at 700 m/s. Watt’s Bath was used as an electrolyte in ED coating meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…6 Metal-ceramic composite coatings can provide effective protection for the base metal. 7 For example, WC-Ni [8][9][10] and WC-Co [11][12][13][14][15] coatings can provide protection for the base metal, where the high hardness of the tungsten carbide enables the coating to withstand the wear of steel strips in motion. This kind of coating is usually prepared by the supersonic flame spraying method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Metal-ceramic composite coatings can provide effective protection for the base metal. 7 For example, WC-Ni [8][9][10] and WC-Co [11][12][13][14][15] coatings can provide protection for the base metal, where the high hardness of the tungsten carbide enables the coating to withstand the wear of steel strips in motion. This kind of coating is usually prepared by the supersonic flame spraying method.…”
Section: Introductionmentioning
confidence: 99%
“…The coating has a higher bonding strength with the substrate. 10,16,17 In our previous study, it was found that the service life of sinker rolls can be increased from 5 to 20 days by preparing coatings on the 316 L stainless steel hot-dip galvanized sinker rolls. 18 To study the actual protective effect of metal-ceramic coatings and the reasons for the eventual failure of the coating, this paper conducted a zinc corrosion test using coated specimens and tested the service life of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…While Gasagara et al [20] compared the experimental results and finite element simulation studies of machining of mild steel work material using high-speed steel tools, Monaghan et al [2] used finite element methods to decide the influence of tungsten carbide as a coating layer on cutting tools to enhance the machining of the difficult-to-machine alloy, Inconel 718. To improve the performance of cutting tools, coating of a tough tool material with a thin layer of a material possessing higher degree of hot hardness and wear resistance is followed [10,21,22]. Coatings to the order of microns differ in the response to peel-off during machining.…”
Section: Introductionmentioning
confidence: 99%